Foreign Direct Investment Between Asian Developing Countries and the EU Member States: The Role of Integration Processes; Bezposŕednie inwestycje zagraniczne miedzy azjatyckimi krajami rozwijajacymi sie a krajami członkowskimi Unii Europejskiej: rola procesoẃ integracyjnych - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2013)
This article discusses the conditions surrounding the flow of foreign direct investment (FDI) between the developing countries of Asia (East Asia, South-East Asia, Southern Asia, and Western Asia) and the countries with membership in the European Union (EU), including the so-called 'new' Member States (EU12). At the intra-regional and inter-regional levels, the flow is especially affected by the world economic crisis, which has effected changes in the positions of the analyzed countries on a global scale. The integration processes taking place in the EU also significantly affect the intensity of FDI flow within the group, while the processes taking place in the developing countries of Asia are not yet sufficiently enough advanced to significantly affect the flow of FDI. Inter-regional FDI flows take place between the subject regions and sub-regions. The observed phenomenon of emerging Asian net exporters of capital in the form of FDI to the European Union may be strengthened by the process of Asian integration. For the new EU Member States the developing Asian countries may constitute an alternative source of capital in the crisis conditions. – – Przedmiotem artykułu sa uwarunkowania przepływoẃ bezposŕednich inwestycji zagranicznych (BIZ) miedzy rozwijajacymi sie krajami Azji (Azji Wschodniej, Azji Południowo-Wschodniej, Azji Południowej i Azji Zachodniej) oraz krajami Unii Europejskiej, w tym nowymi krajami członkowskimi. Na przepływy wewnatrz-regionalne i miedzyregionalne oddziałuje w szczegoĺnosći sytuacja kryzysowa w gospodarce sẃiatowej, zmieniajac pozycje analizowanych grup krajoẃ w skali globalnej. Procesy integracyjne w ramach Unii Europejskiej oddziałuja silnie na intensywnosćṕrzepływoẃ BIZ wewnatrz ugrupowania, podczas gdy procesy te w rozwijajacej sie Azji nie sa jeszcze zaawansowane i ich oddziaływanie na przepływy BIZ jest niewielkie. Miedzy analizowanymi regionami i subregionami dokonuja sie miedzyregionalne przepływy BIZ. Obserwowane zjawisko wyłaniania sie azjatyckich eksporteroẃ netto kapitału w formie BIZ do Unii Europejskiej mozė bycẃzmacniane procesami integracyjnymi. Dla nowych krajoẃ członkowskich UE azjatyckie kraje rozwijajace sie moga stanowicálternatywne zŕod́ło kapitału w warunkach kryzysowych.
Keywords: 330